Glass cloth, prepreg, and printed circuit board

KR103019961B1Active Publication Date: 2026-09-15ASAHI KASEI KOGYO KABUSHIKI KAISHA
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
KR1020237026909
Authority / Receiving Office
KR · KR
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-04-09
Filing Date
2021-10-11
Publication Date
2026-09-15
Estimated Expiration
2041-10-11

Smart Images

  • Figure 112023086992788-PCT00001
    Figure 112023086992788-PCT00001
  • Figure 112023086992788-PCT00002
    Figure 112023086992788-PCT00002
  • Figure 112023086992788-PCT00003
    Figure 112023086992788-PCT00003
Patent Text Reader

Abstract

A glass cloth is provided that is formed by weaving a glass yarn consisting of multiple glass filaments as warp and weft threads, the surface of the glass cloth is surface-treated with a surface treatment agent, and the total carbon extraction amount when the glass cloth is extracted with methanol is greater than 0 and less than or equal to 0.25%.
Need to check novelty before this filing date? Find Prior Art

Description

Technology Field

[0001] The present invention relates to glass cloth, prepreg, and printed circuit board. Background Technology

[0002] Currently, with the increase in performance of information terminals such as smartphones and high-speed communication represented by 5G communication, the dielectric constant and dielectric loss tangent of insulating materials used to reduce transmission loss in high-speed communication printed circuit boards are being significantly reduced.

[0003] Examples of insulating materials for printed circuit boards for high-speed communication are reported in Patent Documents 1 and 2. Specifically, a laminated board is known in which a low dielectric thermosetting resin or thermoplastic resin (hereinafter collectively referred to as "matrix resin"), such as polyphenylene ether with ends modified by vinyl groups or methacrylic oxy groups, is impregnated into a glass cloth and dried to obtain prepregs, which are then laminated and heat-pressurized (Patent Documents 1 and 2). According to Patent Documents 1 and 2, the glass cloth is also required to have a low dielectric constant and a low dielectric loss tangent.

[0004] As a method for reducing the dielectric constant and dielectric loss tangent of glass cloth, Patent Document 3 points out the problem of hydroxyl groups on the glass surface as a factor in the increase of the dielectric loss tangent of glass cloth, and discloses a method for reducing the amount of hydroxyl groups on the glass surface with a surface treatment agent. Prior art literature

[0005] International Publication No. 2019 / 065940, International Publication No. 2019 / 065941, Japanese Patent Publication No. 2020-194888 The problem to be solved

[0006] However, even in Patent Document 3, the improvement in the dielectric loss tangent of silica glass cloth at 10 GHz is 1.0 × 10⁻⁶ -3 Up to 1.0×10 -4...and the improvement effect is considered to be small. In this regard, it is thought that there is room for improvement as there are factors that increase the dielectric loss tangent of the glass cloth in addition to the presence of hydroxyl groups on the glass surface. Accordingly, the present invention aims to provide a glass cloth having a dielectric loss tangent close to the bulk dielectric loss tangent of the glass, and prepregs and printed circuit boards using the same. means of solving the problem

[0007] The inventors, as a result of examining the above problem, discovered that the cause of the increase in the dielectric loss tangent of glass cloth is organic matter remaining in a state of being physically attached to the surface of glass yarn, and thus arrived at the present invention. Specifically, the inventors discovered that the causes include trace amounts of thermally oxidized degraded products of sizing agents that were not completely reduced by heat cleaning, and residues and modified products of surface treatment agents, such as silane coupling agents, which are physically attached without forming a chemical bond with the glass surface and cannot be reduced (e.g. removed) by washing with water, and thus arrived at the present invention. Some embodiments of the present invention are exemplified below.

[0008] [1]

[0009] A glass cloth formed by weaving glass threads composed of multiple glass filaments as warp and weft threads, wherein the surface of the glass cloth is surface-treated with a surface treatment agent, and the total carbon extraction amount when the glass cloth is extracted with methanol is greater than 0 and less than or equal to 0.25%.

[0010] [2]

[0011] A glass cloth described in Item 1, wherein the silicon (Si) content of the glass thread is 95 mass% to 100 mass% in terms of silicon dioxide (SiO2).

[0012] [3]

[0013] A glass cloth described in Item 1 or 2, wherein the Si content of the glass thread is 99.0 mass% to 100 mass% in terms of SiO2.

[0014] [4]

[0015] A glass cloth described in any one of items 1 to 3, wherein the Si content of the glass thread is 99.9 mass% to 100 mass% in terms of SiO2.

[0016] [5]

[0017] The above surface treatment agent is the following general formula (1):

[0018]

[0019] (In Formula (1), X is an organic functional group having at least one of an unsaturated double bond group and an amino group having radical reactivity, Y is each independently an alkoxy group, n is an integer from 1 to 3, and R is each independently a group selected from the group consisting of a methyl group, an ethyl group, and a phenyl group)

[0020] A glass cloth described in any one of items 1 to 4, comprising a silane coupling agent represented by

[0021] [6]

[0022] Glass cloth described in Item 5, wherein X in the above general formula (1) is an organic functional group that does not form salts with ionic compounds.

[0023] [7]

[0024] Glass cloth described in item 5 or 6, wherein X in the above general formula (1) does not contain an amine or ammonium cation.

[0025] [8]

[0026] A glass cloth described in any one of items 5 to 7, wherein X in the above general formula (1) is an organic functional group having one or more methacrylic oxygen groups or acrylic oxygen groups.

[0027] [9]

[0028] A glass cloth described in any one of items 1 to 8, having a total carbon extraction amount of 0.20% or less.

[0029]

[10]

[0030] Glass cloth described in Item 9, having a total carbon extraction amount of 0.10% or less.

[0031]

[11]

[0032] Glass cloth described in Item 10, having a total carbon extraction amount of 0.08% or less.

[0033]

[12]

[0034] Glass cloth described in Item 11, having a total carbon extraction amount of 0.05% or less.

[0035]

[13]

[0036] The bulk dielectric loss tangent of the glass constituting the above glass chamber is greater than 0 and 2.5 × 10 at 10 GHz. -3 Glass cloth described in any one of items 1 to 12, as described below.

[0037]

[14]

[0038] The bulk dielectric loss tangent of the glass constituting the above glass chamber is 2.0 × 10 at 10 GHz. -3 Glass cloth described in Item 13, below.

[0039]

[15]

[0040] The bulk dielectric loss tangent of the glass constituting the above glass chamber is 1.7 × 10⁻⁶ at 10 GHz -3 Glass cloth described in Item 14, Lee Ha-in.

[0041]

[16]

[0042] The bulk dielectric loss tangent of the glass constituting the above glass chamber is 1.5 × 10 at 10 GHz -3 Glass cloth described in Item 15, below.

[0043]

[17]

[0044] The bulk dielectric loss tangent of the glass constituting the above glass chamber is 1.2 × 10⁻⁶ at 10 GHz -3 Glass cloth described in Item 16, below.

[0045]

[18]

[0046] The dielectric loss tangent of the above glass cloth is greater than 0 and greater than 1.0 × 10 at 10 GHz. -3 Glass cloth described in any one of items 1 to 17, as described below.

[0047]

[19]

[0048] A glass cloth described in any one of items 1 to 18, having a total carbon content of 0.010% to 0.380% after methanol extraction.

[0049]

[20]

[0050] A glass cloth described in any one of items 1 to 19, having a total carbon content of 0.013% to 0.250% after methanol extraction.

[0051]

[21]

[0052] A glass cloth described in any one of items 1 to 20, having a total carbon content of 0.015% to 0.180% after methanol extraction.

[0053]

[22]

[0054] A glass cloth described in any one of items 1 to 21, having a total carbon content of 0.018% to 0.150% after methanol extraction.

[0055]

[23]

[0056] A glass cloth described in any one of items 1 to 22, having a total carbon content of 0.020% to 0.100% after methanol extraction.

[0057]

[24]

[0058] A glass cloth described in any one of items 1 to 23, having a total carbon content of 0.020% to 0.500% before methanol extraction.

[0059]

[25]

[0060] A glass cloth described in any one of items 1 to 24, having a total carbon content of 0.022% to 0.400% before methanol extraction.

[0061]

[26]

[0062] A glass cloth described in any one of items 1 to 25, having a total carbon content of 0.023% to 0.300% before methanol extraction.

[0063]

[27]

[0064] A glass cloth described in any one of items 1 to 26, having a total carbon content of 0.024% to 0.200% before methanol extraction.

[0065]

[28]

[0066] A glass cloth described in any one of items 1 to 27, having a total carbon content of 0.025% to 0.100% before methanol extraction.

[0067]

[29]

[0068] A glass cloth described in any one of items 1 to 28, for use as a printed circuit board.

[0069]

[30]

[0070] A prepreg containing a glass cloth as described in any one of items 1 to 29 and a thermosetting resin.

[0071]

[31]

[0072] A printed circuit board comprising the prepreg described in Item 30.

[0073]

[32]

[0074] The following general formula (1):

[0075]

[0076] {In Formula (1), X is an organic functional group having at least one of an unsaturated double bond group and an amino group having radical reactivity, Y is each independently an alkoxy group, n is an integer from 1 to 3, and R is each independently a group selected from the group consisting of a methyl group, an ethyl group, and a phenyl group}

[0077] A method for manufacturing a glass cloth, comprising a process of cleaning a glass cloth surface-treated with a surface treatment agent represented by [a specific agent] with an organic solvent.

[0078]

[33]

[0079] A method for manufacturing glass cloth as described in Item 32, wherein X in the above general formula (1) is an organic functional group that does not form salts with ionic compounds.

[0080]

[34]

[0081] A method for manufacturing glass cloth as described in item 32 or 33, wherein X in the above general formula (1) does not contain an amine or ammonium cation.

[0082]

[35]

[0083] A method for manufacturing glass cloth as described in any one of items 32 to 34, wherein X in the above general formula (1) is an organic functional group having one or more methacryloxy groups or acryloxy groups.

[0084]

[36]

[0085] A method for manufacturing glass cloth as described in any one of items 32 to 35, wherein the organic solvent is methanol. Effects of the invention

[0086] According to the present invention, a glass cloth having a dielectric loss tangent close to the bulk dielectric loss tangent of glass, a prepreg using said glass cloth, and a printed circuit board can be provided. Specific details for implementing the invention

[0087] Hereinafter, embodiments of the present invention (hereinafter referred to as "the present embodiments") will be described in detail; however, the present invention is not limited thereto, and various modifications are possible within the scope of not departing from the gist thereof.

[0088] In the present embodiment, a numerical range described using "to" includes the values ​​before and after "to" within that numerical range. Furthermore, in the present embodiment, regarding numerical ranges described in steps, an upper or lower limit value described in one numerical range may be replaced with an upper or lower limit value of another numerical range described in steps. Additionally, in the present embodiment, an upper or lower limit value described in one numerical range may be replaced with a value shown in the example. Moreover, in the present embodiment, the word "process" is included not only in independent processes but also in cases where it cannot be clearly distinguished from other processes, provided that the purpose of the process is achieved.

[0089] [Glass Cloth]

[0090] The glass cloth of the present embodiment is a glass cloth formed by weaving glass yarns composed of a plurality of glass filaments as warp and weft threads. The glass cloth according to the present embodiment is surface-treated with a surface treatment agent and also has a specific value as the extraction amount during methanol extraction. The surface treatment agent treats the surface of the glass yarn (including glass filaments) as described below.

[0091] [Methanol Extraction Amount]

[0092] The surface-treated glass cloth according to the present embodiment has an extraction amount of 0.25% or less when extracted with methanol. The composition of the surface-treated glass cloth having a dielectric loss tangent close to the bulk dielectric loss tangent of the glass is specified by the methanol extraction amount of 0.25% or less. The methanol extraction amount is determined from the difference in total carbon content (%) between a glass cloth that has not undergone methanol extraction and a glass cloth that has undergone methanol extraction, and is described in detail in the section of the examples. The components extracted by methanol extraction include, for example, unnecessary components attached to the glass cloth that are originally desirable to be reduced (e.g., components derived from sizing agents, or components derived from silane coupling agents that are not chemically bonded to the glass). In other words, the significance of using the methanol extraction amount lies in the fact that these unnecessary components can be indirectly identified using the total carbon content. In addition, in this specification, the amount extracted when glass cloth is extracted with methanol may also be referred to as "total carbon extraction amount."

[0093] In order for the surface-treated glass cloth to exhibit excellent dielectric properties, it is preferable that the methanol extraction amount be less than 0.25%, more preferable that it be 0.20% or less, even more preferable that it be 0.10% or less, even more preferable that it be 0.08% or less, and particularly preferable that it be 0.05% or less. The lower limit of the methanol extraction amount of the surface-treated glass cloth is not particularly limited and, for example, may be 0% or may exceed 0%.

[0094] I do not wish to be bound by theory, but the methanol extract of surface-treated glass cloth is,

[0095] Select a surface treatment agent to suppress the persistence and occurrence of the following (i) or (ii);

[0096] In the glass cloth manufacturing process, conditions such as the heating de-oiling (heating de-gluing) process, residual adhesive reduction process, fixing process, cleaning process, drying process, final cleaning process, and final drying process are optimized.

[0097] As such, it is considered that it is adjusted within the above numerical range.

[0098] (i) Trace amounts of thermally oxidized deteriorated sizing agent remaining in a state of being physically attached to the surface of the glass yarn

[0099] (ii) Residues or modified materials of surface treatment agents that are physically attached without forming chemical bonds with the glass surface and cannot be reduced by washing with water

[0100] [Average filament diameter]

[0101] The average filament diameter of the glass filament is preferably 2.5 to 9.0 μm, more preferably 2.5 to 7.5 μm, even more preferably 3.5 to 7.0 μm, even more preferably 3.5 to 6.0 μm, and particularly preferably 3.5 to 5.0 μm.

[0102] [Type Density]

[0103] The type density of warp and weft yarns constituting the glass cloth is preferably 10 to 120 yarns / inch (=10 to 120 yarns / 25.4 mm), more preferably 40 to 100 yarns / inch, and even more preferably 40 to 100 yarns / inch.

[0104] [Thousands of Weight]

[0105] In addition, the cloth weight (weight per unit area) of the glass cloth is preferably 8 to 250 g / m², more preferably 8 to 100 g / m², even more preferably 8 to 80 g / m², and particularly preferably 8 to 50 g / m².

[0106] [Textile Structure]

[0107] Regarding the weaving structure of glass cloth, although not specifically limited, examples include plain weave, lion weave, satin weave, and twill weave. Among these, a plain weave structure is more preferable.

[0108] [Glass Bell]

[0109] Glass commonly referred to as E glass (alkali-free glass) is used as the glass cloth used in the laminate. Meanwhile, for the glass cloth of the present embodiment, for example, L glass, NE glass, D glass, L2 glass, T glass, silica glass, quartz glass, etc. may be used. From the perspective of dielectric properties, L glass, L2 glass, silica glass, quartz glass, etc. are more preferably used, and among them, silica glass and quartz glass are particularly preferred.

[0110] In that the effect of the present invention is more pronounced as the bulk dielectric loss tangent of the glass is lower, the silicon (Si) content of the glass fiber constituting the glass cloth is preferably in the range of 95 mass% to 100 mass% in terms of silicon dioxide (SiO2), more preferably in the range of 99 mass% to 100 mass%, more preferably in the range of 99.5 mass% to 100 mass%, and particularly preferably in the range of 99.9 mass% to 100 mass%.

[0111] [Glass Bulk Oilfield Loss Tangent]

[0112] The inventors have discovered that in glass species where an increase in dielectric loss tangent is significantly observed due to the presence of thermal oxidation degradation products of sizing agents or residues and modified products of surface treatment agents, an increase in dielectric loss tangent is more likely to occur as the dielectric loss tangent decreases. Accordingly, the range of bulk dielectric loss tangent of glass in which the effects of the present invention are likely to manifest is 2.5 × 10⁻⁶ at 10 GHz. -3 The following is preferable, 2.0×10 -3 The following is more preferable, 1.7×10 -3 The following is more preferable, and 1.5×10 -3The following is more preferable, 1.2×10 -3 The following is particularly desirable. In addition, the lower limit of the bulk dielectric loss tangent of the glass constituting the glass seal of the present embodiment may be "greater than 0" at, for example, 10 GHz.

[0113] In addition, the composition of each glass and the bulk dielectric loss tangent show the following relationship.

[0114] Glass with 99 mass% or more in SiO2 equivalent: Bulk dielectric loss tangent ≤ 1.2 × 10⁻⁶ -3 ;

[0115] Free of 50% or more in SiO2 equivalent, 20% or more in boron dioxide (B2O3) equivalent, and 3% or more in phosphorus pentoxide (P2O5) equivalent: Bulk dielectric loss tangent ≤ 1.7 × 10⁻⁶ -3 ;

[0116] Glass with 50% or more in SiO2 equivalent, 20% or more in B2O3 equivalent, and 0.4% or more in strontium oxide (SrO) equivalent: Bulk dielectric loss tangent ≤ 1.7 × 10⁻⁶ -3

[0117] [Glass Thread and Silane Coupling Agent]

[0118] The glass threads (including glass filaments) constituting the glass cloth are preferably surface-treated with a silane coupling agent. As for the silane coupling agent, for example, the following general formula (1):

[0119]

[0120] {In Formula (1), X is an organic functional group having at least one of an unsaturated double bond group having radical reactivity, such as a radically reactive carbon-carbon double bond, and an amino group; Y is each independently an alkoxy group; n is an integer from 1 to 3; and R is a group selected from the group consisting of methyl, ethyl, and phenyl groups}

[0121] It is preferable to use a silane coupling agent represented by [this].

[0122] It is preferable that the silane coupling agent be nonionic in order to avoid hindering reactivity with the resin. Among nonionic silane coupling agents, a silane coupling agent having at least one group selected from the group consisting of vinyl groups, methacryloxy groups, and acryloxy groups is preferred, and among these, a silane coupling agent having at least one methacryloxy group or an acryloxy group is particularly preferred. By not hindering reactivity with the resin, the heat resistance or reliability of the printed circuit board can be increased.

[0123] In Formula (1), X is an organic functional group having at least one of the unsaturated double bond and the amino group. Accordingly, any of the following are included in the scope of Formula (1): an embodiment in which X has both the unsaturated double bond and the amino group, an embodiment in which X has the unsaturated double bond but not the amino group, and an embodiment in which X does not have the unsaturated double bond but has the amino group.

[0124] In this embodiment, the cause of the increase in the dielectric loss tangent of conventional glass cloth is,

[0125] (i) trace amounts of thermal oxidation degradation of the sizing agent remaining in a state physically attached to the surface of the glass yarn, and

[0126] (ii) Residues or modified materials of surface treatment agents that are physically attached without forming chemical bonds with the glass surface and cannot be reduced by washing with water

[0127] It is based on the observation that there was (i) thermal oxidation deterioration product or (ii) modified product. In the view of suppressing the occurrence of (i) thermal oxidation deterioration product or (ii) modified product, it is preferable that X in general formula (1) is an organic functional group that does not form salts with ionic compounds. Furthermore, in the view of reactivity with the matrix resin, it is more preferable that X in general formula (1) is an organic functional group having one or more methacryloxy groups or acryloxy groups. In addition, in the view of making it easier to express the effects of the present invention, it is preferable that X in general formula (1) does not contain amines such as primary amines, secondary amines, tertiary amines, etc., or ammonium cations such as quaternary ammonium cations, etc.

[0128] Regarding Y in the above general formula (1), any form can be used as the alkoxy group, but for stable treatment of glass cloth, an alkoxy group having 1 to 5 carbon atoms (1, 2, 3, 4 or 5 carbon atoms) is preferred.

[0129] As a surface treatment agent, the silane coupling agent represented by general formula (1) may be used as a single agent, or may be used in combination with two or more silane coupling agents in which X in general formula (1) is different. In addition, as the silane coupling agent represented by general formula (1), known single agents such as vinyltrimethoxysilane, 3-methacryloxypropyltrimethoxysilane, acryloxypropyltrimethoxysilane, 3-acryloxypropyltrimethoxysilane, 5-hexenyltrimethoxysilane, or mixtures thereof may be used.

[0130] The molecular weight of the silane coupling agent is preferably 100 to 600, more preferably 150 to 500, and even more preferably 200 to 450. Among these, it is particularly preferable to use two or more types of silane coupling agents with different molecular weights. By treating the glass surface using two or more types of silane coupling agents with different molecular weights, the density of the treatment agent on the glass surface increases, and the reactivity with the matrix resin tends to be further improved.

[0131] [Method for manufacturing glass cloth]

[0132] The method for manufacturing glass cloth according to the present embodiment is not particularly limited, but, for example, the following process:

[0133] A heating and desalting process for desalting glass cloth by heating it at any temperature between 300°C and 1000°C, and

[0134] A coating process for attaching a silane coupling agent to the surface of a glass filament using a treatment solution with a concentration of 0.1 to 3.0 wt%, and

[0135] A fixation process for fixing a silane coupling agent to the surface of a glass filament by heat drying, and

[0136] A cleaning process for cleaning a silane coupling agent that has not formed a chemical bond with the surface of a glass filament with water, and

[0137] A drying process (heat drying process) for heating and drying the glass cloth after cleaning, and

[0138] A finishing cleaning process that reduces residues and modified silane coupling agents that do not form chemical bonds with the surface of glass filaments, which could not be reduced by water.

[0139] Examples of methods containing [the substance] may be provided. Additionally, the coating process, fixing process, cleaning process, and treatment cleaning process may be performed on the glass yarn before the weaving process to obtain glass cloth, or on the glass cloth after the weaving process. The method for manufacturing glass cloth may also, if necessary, include a residual adhesive reduction process to reduce the sizing agent modifications remaining from the heating desalting process, and a fiber opening process to open the glass yarns of the glass cloth after the weaving process. Additionally, if the cleaning process is performed after the weaving process, the cleaning process may also serve as the fiber opening process by using a high-pressure water spray, etc. Furthermore, the composition of the glass cloth does not usually change before or after fiber opening.

[0140] It is believed that by the above manufacturing method, after excluding the attached organic material that raises the dielectric loss tangent, a silane coupling agent layer can be formed on the surface of each glass filament constituting the glass thread.

[0141] Processes for reducing residual adhesive include dry cleaning such as plasma irradiation and UV ozone; wet cleaning such as high-pressure water cleaning, organic solvent cleaning, nano-bubble water cleaning, and ultrasonic rinsing; and heat cleaning at a temperature higher than that of a heat desalination process, and a combination of these may be used. However, for the process for reducing residual adhesive, short-time heat cleaning in which glass cloth is passed through a heating furnace of 800°C or higher in a roll-to-roll manner is preferred.

[0142] Methods for applying the treatment solution to the glass cloth in the coating process include (a) a method of storing the treatment solution in a bath and immersing and passing the glass cloth through it (hereinafter referred to as the "immersion method"), and (b) a method of directly applying the treatment solution to the glass cloth using a roll coater, die coater, or gravure coater. When applying using the immersion method of (a) above, it is preferable to select the immersion time of the glass cloth in the treatment solution to be 0.5 seconds or more and 1 minute or less.

[0143] In addition, known methods such as hot air and electromagnetic waves can be used to heat and dry the solvent after applying the treatment solution to the glass cloth.

[0144] The heating and drying temperature is preferably 80°C or higher, and more preferably 90°C or higher, so that the reaction between the silane coupling agent and the glass is sufficiently carried out. In addition, the heating and drying temperature is preferably 300°C or lower, and more preferably 180°C or lower, in order to prevent deterioration of the organic functional groups of the silane coupling agent.

[0145] The final cleaning process is not particularly limited as long as it is a method capable of reducing residues and modified substances of the silane coupling agent that do not form chemical bonds with the surface of the glass filament and cannot be reduced by water, but examples include cleaning in an organic solvent. In addition, in another embodiment of the present invention, a method for manufacturing a glass cloth is provided, comprising a process of cleaning a glass cloth surface-treated with a surface treatment agent represented by the general formula (1) with an organic solvent. According to this manufacturing method, even if raw materials such as quartz glass are used, the dielectric loss tangent of the resulting glass cloth can be made close to the bulk dielectric loss tangent.

[0146] For the final cleaning process, in order to reduce silane coupling agent residues and modified substances that cannot be reduced in water, it is preferable to clean using a highly hydrophobic organic solvent or an organic solvent having high affinity for hydroxyl-containing silane coupling agent residues and modified substances. Known cleaning methods such as immersion or shower spraying may be used, and heating or cooling may be applied as necessary. To prevent the re-attachment of dissolved glass cloth deposits, it is preferable to reduce excess solvent on the glass cloth after cleaning using a throttle roller or the like before final drying. The organic solvent used is not particularly limited, but for example, as a highly hydrophobic organic solvent,

[0147] Saturated chain aliphatic hydrocarbons such as n-pentane, i-pentane, n-hexane, i-hexane, n-heptane, i-heptane, n-octane, i-octane, 2,2,4-trimethylpentane (isooctane), n-nonane, i-nonane, n-decane, i-decane, 2,2,4,6,6-pentamethylheptane (isododecane);

[0148] Saturated cyclic aliphatic hydrocarbons such as cyclopentane, cyclohexane, methylcyclohexane, dimethylcyclohexane, ethylcyclohexane, etc.;

[0149] Aromatic hydrocarbons such as benzene, toluene, xylene, ethylbenzene, diethylbenzene, trimethylbenzene, and triethylbenzene;

[0150] Halogen-containing solvents such as chloroform, dichloromethane, and dichloroethane

[0151] Examples include the following. Organic solvents with high affinity for silane coupling agent modified products include alcohols such as methanol, ethanol, and butanol; ketones such as acetone and methyl ethyl ketone; and ethers such as methyl ethyl ether and diethyl ether;

[0152] Amides such as N,N-dimethylformamide, N,N-dimethylacetamide, etc.;

[0153] Examples include dimethyl sulfoxide. Among these, aromatic hydrocarbons, alcohols, or ketones are preferred from the perspective of making the dielectric loss tangent of the obtained glass cloth close to the bulk dielectric loss tangent, and methanol is more preferred.

[0154] In order to reduce the organic solvent after washing, it is preferable for the method of manufacturing glass cloth to include a drying process, and from the perspective of ease of reducing the organic solvent by drying, it is preferable for the organic solvent used for washing to have a boiling point of 120°C or lower. Known methods such as heat drying and air drying can be used for drying the organic solvent.

[0155] When performing heat drying to reduce organic solvent, known techniques may be used, but for safety reasons, hot air drying using low-pressure steam or a heat medium oil as a heat source is preferred. The drying temperature is preferably above the boiling point of the cleaning solvent, and is preferably 180°C or lower from the perspective of suppressing the deterioration of the silane coupling agent.

[0156] Furthermore, regarding the fiber opening method for the fiber opening process, although not specifically limited, examples include opening the glass cloth using spray water (high-pressure water opening), a vibro washer, ultrasonic water, or a mangle. During this fiber opening process, there is a tendency to reduce air permeability by lowering the tension applied to the glass cloth. Additionally, to suppress the reduction in tensile strength of the glass cloth caused by the fiber opening process, it is desirable to implement measures such as reducing friction of the contact member during glass yarn weaving, optimizing the binding agent, and increasing the adhesion amount.

[0157] The method for manufacturing glass cloth may include any process even after the fiber opening process. Any process is not particularly limited, but an example is a slit processing process.

[0158] [Prypreg]

[0159] The prepreg of the present embodiment contains at least the glass cloth and a matrix resin impregnated in the glass cloth. By doing so, a prepreg with fewer voids can be provided.

[0160] As the matrix resin, both thermosetting resins and thermoplastic resins can be used.

[0161] As for thermosetting resins, they are not particularly limited, but for example,

[0162] a) an epoxy resin formed by reacting and curing a compound having an epoxy group and a compound having at least one of an amino group, a phenol group, an acid anhydride group, a hydrazide group, an isocyanate group, a cyanate group, and a hydroxyl group that reacts with the epoxy group, either without a catalyst or by adding a catalyst having reaction catalytic ability such as an imidazole compound, a tertiary amine compound, a urea compound, or a phosphorus compound;

[0163] b) A radical polymerization type cured resin formed by curing a compound having at least one of an allyl group, a methacrylic group, and an acrylic group using a pyrolysis type catalyst or a photolysis type catalyst as a reaction initiator;

[0164] c) Maleimide triazine resin formed by reacting a compound having a cyanate group with a compound having a maleimide group and curing the result;

[0165] d) a thermosetting polyimide resin formed by reacting a maleimide compound with an amine compound and curing it;

[0166] e) Examples include benzoxazine resins formed by cross-linking and curing a compound having a benzoxazine ring by heat polymerization.

[0167] In addition, thermoplastic resins are not particularly limited, but examples include polyphenylene ether, modified polyphenylene ether, polyphenylene sulfide, polysulfone, polyethersulfone, polyarylate, aromatic polyamide, polyetheretherketone, thermoplastic polyimide, insoluble polyimide, polyamideimide, fluoropolymer, etc.

[0168] In addition, in this embodiment, a thermosetting resin and a thermoplastic resin may be used in combination. Also, the prepreg may include an inorganic filler as desired. It is preferable that the inorganic filler be used in combination with the thermosetting resin. The inorganic filler may be, for example, aluminum hydroxide, zirconium oxide, calcium carbonate, alumina, mica, aluminum carbonate, magnesium silicate, aluminum silicate, silica, talc, glass staple fibers, aluminum borate, silicon carbide, etc.

[0169] [Printed Wiring Board]

[0170] The printed circuit board of the present embodiment contains the prepreg. By doing so, a printed circuit board with excellent insulation reliability can be provided.

[0171] [Yuri Cloth's Dielectric Loss Tangent Measurement Method]

[0172] The dielectric property evaluation method of the present embodiment includes a process for measuring the dielectric properties of a cloth using a resonance method. The measurement method in the above measurement process is not limited to any specific method as long as it is a measurement method utilizing the resonance method. According to the present measurement method, measurement can be performed simply and with high precision compared to conventional measurement methods that evaluate dielectric properties by fabricating a substrate as a measurement sample. The reason why the dielectric properties of a cloth can be measured simply and with high precision by using the resonance method is not limited to theory, but is that the resonance method is suitable for evaluating low-loss materials in the high-frequency region. Dielectric property evaluation methods other than the resonance method include the lumped constant method and the reflection transmission method. The lumped constant method has the problem that the operation is very cumbersome because it is necessary to form a capacitor by sandwiching the measurement sample between two electrodes. Furthermore, in the reflection transmission method, when evaluating low-loss materials, the influence of port matching characteristics appears strongly, making it difficult to evaluate the dielectric loss tangent of the sample with high precision. For the above reasons, the resonance method is preferred for the dielectric property evaluation method of the present cloth.

[0173] In this measurement process, preferred measuring instruments utilizing the resonance method include split-cylinder resonators, open-type resonators, and NRD-guided excitation dielectric resonators. However, as long as the principle of the resonance method is utilized, the dielectric properties of the cloth may be evaluated using instruments other than the above-mentioned measuring instruments.

[0174] To measure the dielectric properties of the above cloth used for high-speed communication printed circuit boards, the measurable range of the measuring instrument is, for dielectric constant (Dk) and dielectric loss tangent (Df), Dk = 1.1Fm, respectively. -1 to 50Fm -1 , Df=1.0×10 -6 Up to 1.0×10 -1 This is desirable, and Dk=1.5Fm -1to 10Fm -1 , Df=1.0×10 -5 Up to 5.0×10 -1 This is more desirable, and Dk=2.0Fm -1 to 5Fm -1 , Df=5.0×10 -5 Up to 1.0×10 -2 It is more desirable.

[0175] It is preferable that the measurable frequency of the measuring device be 10 GHz or higher. If the frequency is 10 GHz or higher, it is possible to evaluate the characteristics in the frequency range assumed when actually used as a glass cloth for a printed circuit board for high-speed communication.

[0176] In order to measure the dielectric properties of the cloth over a larger area and determine whether the measurement result falls within the range of a preset reference value, it is preferable that the measurement area of ​​the measurement method be 10 mm² or larger. It is more preferable that the measurement area of ​​the measurement method be 15 mm² or larger, and even more preferable that it be 20 mm² or larger.

[0177] The thickness of the measurable sample is not particularly limited, but is preferably 3 µm to 300 µm, more preferably 5 µm to 200 µm, and even more preferably 7 µm to 150 µm.

[0178] [Measurement of Bulk Dielectric Loss Tangent]

[0179] The bulk dielectric loss tangent of the glass constituting the glass cloth can be measured by a glass plate with a thickness of 300 μm or less using the same method as the dielectric loss tangent measurement of the glass cloth. The glass cloth according to the present embodiment is preferably used as a substrate for a printed circuit board. In addition, the bulk dielectric loss tangent of the glass constituting the glass seal is 2.5 × 10⁻⁶ at 10 GHz. -3 The following is preferable, 2.0×10 -3 The following is more preferable, 1.7×10 -3 The following is more preferable, and 1.5×10 -3The following is more preferable, 1.2×10 -3 Less than or equal to 1.0×10 -3 The following is particularly desirable. According to this, in the manufacture of a printed circuit board substrate, it becomes easier to make the dielectric loss tangent of the glass cloth close to the bulk dielectric loss tangent of the glass.

[0180] [Total carbon content of glass cloth before methanol extraction]

[0181] The total carbon content of the glass cloth prior to methanol extraction is preferably 0.020% to 0.500%, more preferably 0.022% to 0.400%, even more preferably 0.023% to 0.300%, more preferably 0.024% to 0.200%, and particularly preferably 0.025% to 0.100%. According to this, it is easy to obtain an embodiment in which the amount of the silane coupling agent, which is physically attached and should ideally be reduced, is reduced while having good insulation reliability.

[0182] [Total carbon content of glass cloth after methanol extraction]

[0183] The total carbon content of the glass cloth after methanol extraction is preferably 0.010% to 0.380%, more preferably 0.013% to 0.250%, even more preferably 0.015% to 0.180%, more preferably 0.018% to 0.150%, and particularly preferably 0.020% to 0.100%. According to this, it is easy to obtain an embodiment in which the amount of the silane coupling agent, which is physically attached and should ideally be reduced, is reduced while having good insulation reliability.

[0184] [Relationship between methanol extraction and the glass cloth of the present embodiment]

[0185] As explained above, the glass cloth of the present embodiment includes, as one of the requirements, a total carbon extraction amount greater than 0 and less than or equal to 0.25% when extracted with methanol.

[0186] In addition, the present embodiment includes a glass cloth in which the total carbon content of the glass cloth before methanol extraction is within the above range, and also includes a glass cloth in which the total carbon content of the glass cloth after methanol extraction is within the above range.

[0187] Examples

[0188] Next, the present invention will be explained in more detail through examples and comparative examples. The present invention is not limited in any way by the following examples. Various evaluation methods are also described below.

[0189] [Method for Measuring the Thickness of Glass Cloth]

[0190] In accordance with 7.10 of JIS R 3420, a micrometer was used to quietly rotate the spindle and lightly contact it parallel to the measuring surface, and the scale was read after the ratchet clicked three times. In addition, JIS R 3420 specifies general test methods for products such as glass long fibers and glass cloths using glass long fibers.

[0191] [Method for Measuring Weight per Unit Area (Thousand Weights)]

[0192] The weight per unit area of ​​the cloth was determined by cutting the cloth into a predetermined size and dividing the weight by the sample area. In this example or comparative example, the weight per unit area of ​​each glass cloth was determined by cutting the glass cloth into a size of 10 cm² and measuring its weight.

[0193] [Converted Thickness]

[0194] Since glass cloth is a discontinuous planar body composed of air and glass, the converted thickness required for measurement by the resonance method was calculated by dividing the weight per unit area of ​​each glass cloth by its density.

[0195] Converted thickness (㎛) = Weight per unit area (g / m²) ÷ Density (g / cm³)

[0196] [Method for Measuring the Genetic Loss Tangent]

[0197] In accordance with IEC 62562, the dielectric loss tangent of each glass cloth was measured. Specifically, glass cloth samples sampled to the size required for measurement at each resonator were humidified by storing them in a constant temperature and humidity oven at 23°C and 50% RH for at least 8 hours. Subsequently, dielectric properties were measured using a split cylinder resonator (manufactured by EM Labs) and an impedance analyzer (manufactured by Agilent Technologies). Measurements were performed five times for each sample, and the average value was calculated. Additionally, the thickness of each sample was measured using the above-mentioned converted thickness. Furthermore, IEC 62562 specifies a method for measuring dielectric properties in the microwave range for fine ceramic materials used as dielectric substrates, primarily for microwave circuits.

[0198] [Total Carbon Content of Glass Cloth]

[0199] The surface-treated glass cloth was heated at approximately 800°C for 1 minute, and the amount of carbon dioxide in the generated gas was measured by gas chromatography to determine the amount of carbon dioxide in the generated gas. The total carbon content of the surface-treated glass cloth was determined by using the amount of carbon dioxide generated when a predetermined amount of acetanilide (C8H9NO) was similarly heated at approximately 800°C for 1 minute as a comparison. A SUMIGRAPH NC-90A (manufactured by Sumika Bunseki Center) was used for the measurement.

[0200] Molecular weight of acetanilide = 135.17

[0201] Carbon ratio of acetanilide = 71.09%

[0202] That is, the total carbon content of the glass cloth was calculated based on the following formula.

[0203] Total carbon content of glass cloth =

[0204] [{Mass of acetanilide × (Carbon ratio of acetanilide / 100)} / Peak area of ​​carbon dioxide originating from acetanilide] × {(Peak area of ​​carbon dioxide originating from glass cloth / Mass of glass cloth) × 100}

[0205] In addition, when determining the total carbon content of the glass cloth before methanol extraction, the glass cloth before methanol extraction can be used as the measurement target, and when determining the total carbon content of the glass cloth after methanol extraction, the glass cloth after methanol extraction can be used as the measurement target.

[0206] [Method for Measuring Methanol Extraction Amount]

[0207] The amount of methanol extracted from the glass cloth was determined from the difference in total carbon content (%) between the glass cloth that was not methanol extracted and the glass cloth that was methanol extracted. Methanol extraction was performed by immersing 5 mg of glass cloth in 100 ml of methanol at room temperature for 1 minute. This reduced the surface treatment agent physically attached to the glass cloth. The total carbon content of the glass cloth was measured using a SUMIGRAPH NC-90A (manufactured by Sumika Bunseki Center).

[0208] (Example 1)

[0209] As the warp, a silica glass yarn with an average filament diameter of 5.0 μm, 100 filaments, and a water content of 1.0 Z was used, and as the weft, a silica glass yarn with an average filament diameter of 5.0 μm, 100 filaments, and a water content of 1.0 Z was used. Then, using an air jet loom, a glass cloth was woven with a thread density of 66 warp threads / 25 mm and 68 weft threads / 25 mm. The resulting machine was heat-treated at 600°C for 2 hours to perform desizing. Subsequently, the glass cloth was immersed in a treatment solution in which 0.9% of the silane coupling agent 3-methacryloxypropyltrimethoxysilane Z6030 (manufactured by Dow Toray) was dispersed in pure water adjusted to pH=3 with acetic acid. After immersion, the glass cloth was heat-dried at 110°C for 1 minute to fix the silane coupling agent. The dried glass cloth was washed with water and dried at 110°C for 1 minute, and then immersed in methanol to perform a final cleaning of the glass cloth, thereby reducing modified silane coupling agents that did not form chemical bonds with the surface of the glass filament. By drying at 110°C for 1 minute after the final cleaning, glass cloth A with reduced modified physically attached silane coupling agents was obtained.

[0210] (Example 2)

[0211] Glass cloth B with reduced modifications of the physically attached silane coupling agent was obtained by performing the same procedure as in Example 1, except that the heating and drying time of the fixation process was set to 5 minutes.

[0212] (Example 3)

[0213] Glass cloth C with reduced modified physical silane coupling agent was obtained by performing the same procedure as in Example 1, except that the heating and drying time of the fixation process was set to 10 minutes.

[0214] (Example 4)

[0215] Glass cloth D with reduced physical attachment of modified silane coupling agent was obtained by following the same procedure as in Example 2, except that the organic solvent for the final cleaning process was toluene.

[0216] (Example 5)

[0217] Glass cloth E with reduced physical attachment of modified silane coupling agent was obtained by following the same procedure as in Example 2, except that the organic solvent for the final cleaning process was acetone.

[0218] (Example 6)

[0219] Glass cloth F was obtained in which the modified product of the physically attached silane coupling agent and the trace amount of thermal oxidation deterioration of the sizing agent were reduced, by performing additional heating at 800°C for 15 seconds after the desalination process to reduce the residual adhesive, and by doing the same as in Example 1 except that the drying temperature in the drying process was set to 130°C.

[0220] (Example 7)

[0221] Glass cloth G was obtained in which the modified product of the physically attached silane coupling agent and the thermal oxidation deterioration product of the trace amount of sizing agent were reduced by performing a heating degreasing process at 800°C for 30 seconds and, except that the residual adhesive reduction was not performed, in the same manner as in Example 6.

[0222] (Example 8)

[0223] Glass cloth H, in which the modified product of the physically attached silane coupling agent and the trace amount of thermal oxidation deterioration product of the sizing agent were reduced, was obtained in the same manner as in Example 3, except that the residual adhesive was reduced by performing an additional heating of 15 seconds at 800°C after a desalting process of heating at 360°C for 48 hours.

[0224] (Example 9)

[0225] Glass cloth I with reduced physical attachment of modified silane coupling agent was obtained in the same manner as in Example 7, except that a treatment solution in which 0.9% of 5-hexenyltrimethoxysilane; Z6161 (manufactured by Dow Toray) was dispersed as a silane coupling agent was used.

[0226] (Example 10)

[0227] Glass cloth J with reduced physical attachment of modified silane coupling agent was obtained in the same manner as in Example 7, except that a treatment solution in which 0.9% of 3-acryloxypropyltrimethoxysilane; KBM-5103 (manufactured by Shin-Etsu Silicon Co., Ltd.) was dispersed as a silane coupling agent was used.

[0228] (Example 11)

[0229] Glass cloth K with reduced physical attachment of modified silane coupling agents was obtained in the same manner as in Example 7, except that a treatment solution was used in which 0.45% of 5-hexenyltrimethoxysilane; Z6161 (manufactured by Dow Toray) and 0.45% of 3-methacryloxypropyltrimethoxysilane; Z6030 (manufactured by Dow Toray) were dispersed as silane coupling agents.

[0230] (Example 12)

[0231] Glass cloth L with reduced physical attachment of modified silane coupling agents was obtained in the same manner as in Example 7, except that a treatment solution was used in which 0.45% of 3-acryloxypropyltrimethoxysilane; KBM-5103 (manufactured by Shin-Etsu Silicon Co., Ltd.) and 0.45% of 3-methacryloxypropyltrimethoxysilane; Z6030 (manufactured by Dow Toray Co., Ltd.) were dispersed as silane coupling agents.

[0232] (Comparative Example 1)

[0233] The raw material obtained in Example 1 was heat-treated at 360°C for 48 hours to perform desalination. Subsequently, a glass cloth was immersed in a treatment solution in which 0.9% of the silane coupling agent, 3-methacryloxypropyltrimethoxysilane Z6030 (manufactured by Dow Toray), was dispersed in pure water adjusted to pH=3 with acetic acid. After mixing, the glass cloth was heated and dried at 110°C for 1 minute to fix the silane coupling agent. The dried glass cloth was washed with water and dried at 110°C for 1 minute; without performing a final washing process or a final drying process, glass cloth I was obtained.

[0234] (Comparative Example 2)

[0235] Glass cloth J was obtained in the same manner as Comparative Example 1, except that the heating and drying time of the fixing process was set to 5 minutes.

[0236] (Comparative Example 3)

[0237] Glass cloth K was obtained in the same manner as Comparative Example 1, except that the heating and drying time of the fixing process was set to 10 minutes.

[0238] (Comparative Example 4)

[0239] Glass cloth L was obtained in the same manner as Comparative Example 1, except that the heating and degreasing process was carried out at 800°C for 15 seconds.

[0240] The manufacturing conditions and evaluation results of the examples and comparative examples are shown in Table 1.

[0241]

[0242]

[0243] Industrial applicability

[0244] The glass cloth of the present invention has industrial applicability as a substrate used in printed circuit boards used in the electronic and electrical fields.

Claims

Claim 1 A glass cloth formed by weaving glass yarns composed of multiple glass filaments as warp and weft threads, wherein the surface of the glass cloth is surface-treated with a surface treatment agent containing a silane coupling agent, the total carbon extraction amount when the glass cloth is extracted with methanol is greater than 0 and less than or equal to 0.25%, and the bulk dielectric loss tangent of the glass constituting the glass yarn is greater than 0 and 2.5 x 10 at 10 GHz. -3 Lee Ha-in, Glass Cloth. Claim 2 A glass cloth according to claim 1, wherein the silicon (Si) content of the glass thread is 95 mass% to 100 mass% in terms of silicon dioxide (SiO2). Claim 3 A glass cloth according to claim 1, wherein the Si content of the glass thread is 99.0 mass% to 100 mass% in terms of SiO2. Claim 4 A glass cloth according to claim 1, wherein the Si content of the glass thread is 99.9 mass% to 100 mass% in terms of SiO2. Claim 5 In claim 1, the surface treatment agent is the following general formula (1): A glass cloth comprising the above silane coupling agent represented by (wherein in formula (1), X is an organic functional group having at least one of an unsaturated double bond group and an amino group having radical reactivity, Y is each independently an alkoxy group, n is an integer from 1 to 3, and R is each independently a group selected from the group consisting of a methyl group, an ethyl group and a phenyl group). Claim 6 In paragraph 5, X in the above general formula (1) is an organic functional group that does not form a salt with an ionic compound, a glass cloth. Claim 7 In paragraph 5, a glass cloth in which X in the above general formula (1) does not contain an amine or ammonium cation. Claim 8 In claim 5, a glass cloth in which X in the above general formula (1) is an organic functional group having one or more methacrylate and acryloxy groups. Claim 9 A glass cloth according to claim 1, wherein the total carbon extraction amount is 0.20% or less. Claim 10 In claim 9, a glass cloth having a total carbon extraction amount of 0.10% or less. Claim 11 In item 10, a glass cloth having a total carbon extraction amount of 0.08% or less. Claim 12 In claim 11, a glass cloth having a total carbon extraction amount of 0.05% or less. Claim 13 In claim 1, the bulk dielectric loss tangent of the glass constituting the glass chamber is 2.0 × 10 at 10 GHz. -3 Lee Ha-in, Glass Cloth. Claim 14 In paragraph 13, the bulk dielectric loss tangent of the glass constituting the glass chamber is 1.7 × 10 at 10 GHz. -3 Lee Ha-in, Glass Cloth. Claim 15 In paragraph 14, the bulk dielectric loss tangent of the glass constituting the glass chamber is 1.5 × 10 at 10 GHz. -3 Lee Ha-in, Glass Cloth. Claim 16 In paragraph 15, the bulk dielectric loss tangent of the glass constituting the glass chamber is 1.2 × 10⁻⁶ at 10 GHz. -3 Lee Ha-in, Glass Cloth. Claim 17 In claim 1, the dielectric loss tangent of the glass cloth is greater than 0 and greater than 1.0 × 10 at 10 GHz. -3 Lee Ha-in, Glass Cloth. Claim 18 A glass cloth according to claim 1, wherein the total carbon content of the glass cloth after methanol extraction is 0.010% to 0.380%. Claim 19 A glass cloth according to claim 1, wherein the total carbon content of the glass cloth after methanol extraction is 0.013% to 0.250%. Claim 20 A glass cloth according to claim 1, wherein the total carbon content of the glass cloth after methanol extraction is 0.015% to 0.180%. Claim 21 A glass cloth according to claim 1, wherein the total carbon content of the glass cloth after methanol extraction is 0.018% to 0.150%. Claim 22 Glass cloth according to claim 1, wherein the total carbon content of the glass cloth after methanol extraction is 0.020% to 0.100%. Claim 23 A glass cloth according to claim 1, wherein the total carbon content of the glass cloth prior to methanol extraction is 0.020% to 0.500%. Claim 24 A glass cloth according to claim 1, wherein the total carbon content of the glass cloth prior to methanol extraction is 0.022% to 0.400%. Claim 25 A glass cloth according to claim 1, wherein the total carbon content of the glass cloth prior to methanol extraction is 0.023% to 0.300%. Claim 26 A glass cloth according to claim 1, wherein the total carbon content of the glass cloth prior to methanol extraction is 0.024% to 0.200%. Claim 27 A glass cloth according to claim 1, wherein the total carbon content of the glass cloth prior to methanol extraction is 0.025% to 0.100%. Claim 28 In paragraph 1, a glass cloth for use as a printed circuit board. Claim 29 A prepreg containing a glass cloth as described in any one of claims 1 to 28 and a thermosetting resin. Claim 30 A printed circuit board comprising the prepreg described in paragraph 29. Claim 31 The following general formula (1): The process comprises cleaning a glass cloth surface-treated with a surface treatment agent represented by {wherein X is an organic functional group having at least one of an unsaturated double bond group and an amino group having radical reactivity, Y is each independently an alkoxy group, n is an integer from 1 to 3, and R is each independently a group selected from the group consisting of a methyl group, an ethyl group, and a phenyl group} with an organic solvent, wherein, after cleaning, the bulk dielectric loss tangent of the glass constituting the glass thread of the glass cloth is greater than 0 at 10 GHz and 2.5 x 10 -3 Method for manufacturing glass cloth, Lee Ha-in. Claim 32 A method for manufacturing glass cloth according to claim 31, wherein X in the above general formula (1) is an organic functional group that does not form salts with ionic compounds. Claim 33 A method for manufacturing glass cloth according to claim 31 or 32, wherein X in the general formula (1) above does not contain an amine or ammonium cation. Claim 34 A method for manufacturing glass cloth according to claim 31 or 32, wherein X in the general formula (1) is an organic functional group having one or more methacryloxy groups or acryloxy groups. Claim 35 A method for manufacturing glass cloth according to claim 31 or 32, wherein the organic solvent is methanol. Claim 36 delete

Citation Information

Patent Citations

  • Epoxy resin composition, prepreg, cured body, sheet-like molded body, laminate and multilayer laminate

    KR101383434B1

  • Laminates for prepregs and circuit boards

    KR1020200110424A

  • Low dielectric glass composition, fibers, and article

    US11339083B2

  • Prepreg, multilayer wiring board and electronic parts using same

    KR100975161B1

  • Prepreg having thin quartz glass cloth, electronic part using cured products of prepreg, and laminate, printed wiring board and multilayer printed wiring board using the same

    KR101129010B1